Numerical Analysis of Translational Vibration Reduction Response on Drilling Process due to Additional Mass-Rubber Dynamic Vibration Absorber (MR-DVA) - Dika Andini Suryandari; Wiwiek Hendrowati (The International Journal of Mechanical Engineering and Sciences, 2022)
Machining is an important part of the industry, one of which is the drilling process. The drilling process is utilized in the making of holes in a material. When the drill-bit touches the material, it causes a vibration that can affect the quality of the hole surface. Therefore, the analysis of the addition of MR-DVA with a natural frequency of 1,630.2 Hz on a workpiece Aluminium Alloy 7075-T6 as the main system is conducted. Simulations were carried out in the natural frequency range of 1,675 Hz – 1,680 Hz with various workpiece dimension ratios of 2⁄5, 3⁄5, 4⁄5, and 5⁄5, along with the different ratios of an MR-DVA placement between the clamp and hole of 1⁄4, 2⁄4, and 3⁄4. Based on the conducted simulation, it has been found that the MR-DVA with a mass ratio of 1⁄20 can dampen well. The largest reduction for a workpiece dimension ratio of 2⁄5 with an MR-DVA placement ratio of 1⁄4 is 92%. In contrast, the smallest reduction for a workpiece dimension ratio of 3⁄5 is 7.2%. These are because the damping area and the increase in the workpiece's dimensions ratio are inverses, affecting the workpiece area that touches the clamp.